Diseño e implementación de un prototipo de red comunitaria para la aplicación de un sistema de mensajería instantánea mediante tecnología LoRaWAN para áreas sin conectividad durante emergencias - Quisatagsi Herrera, Cristopher Guillermo (2024)
The provision of a communication system independent of the infrastructure as well as telecommunications and electricals supposes currently a great contribution for communities with areas without connectivity, especially in cases of disasters and emergencies. Therefore, the objective of the present work is the design and implementation of a community network prototype for the application of an instant messaging system using LoRaWAN technology. During emergency situations, this prototype seeks to achieve long-range communications and to be self-sufficient in terms of energy. Likewise, for the execution of the communication system, TTGO LoRa32 development cards are used, which act as a mesh node and ensure that users connect and can transmit or receive messages through a chat interface. This communication network has fixed nodes that integrate rechargeable batteries through solar panels and also features mobile nodes that guarantee flexibility and extended coverage. Once the prototype has been implemented in the rural neighborhoods of Moyococha, Santorum and Uchima in the parish of Vilcabamba, the performance of the network is evaluated in terms of message transmission capacity, energy consumption, coverage, and security of the implemented model. The project results show that the messaging system can transmit and receive encrypted messages of up to 200 bytes between several nodes within the mesh network. The maximum effective communication distance between two individual nodes is 2 km, which ensures a fast transmission and low power consumption with a high data rate for messages, achieving that the prototype messaging system implemented in the study area is effective and functional, providing a viable solution for communication in rural areas and in emergency situations. Keywords: community network, instant messaging, LPWAN, Mesh, LoRa.